Recent Advances and Challenges in Obtaining Stable CsPbX3 (X = Cl, Br, and I) Nanocrystals Toward White Light-Emitting Applications. (1st October 2021) - Grandhi, G. Krishnamurthy; Mokurala, Krishnaiah; Han, Joo Hyeong; Bin Cho, Han; Han, Ju Yeon; Im, Won Bin
Abstract : Inorganic halide perovskite (CsPbX3, X = Cl, Br, and I) nanocrystals (PNCs) have been highly sought-after materials in recent years owing to their numerous applications in optoelectronic devices. One such application is white light generation for displays and low-cost light sources. Nevertheless, the poor structural and chemical stabilities of these NCs under environmental factors, such as moisture and oxygen, hinder the fabrication of white light-emitting devices. The improved stability of halide PNCs has been mainly achieved by encapsulating them in robust matrices such as oxide materials, inorganic glass, and metal–organic frameworks. This review summarizes how various encapsulating strategies improve the structural stability of halide PNCs and preserve their bright luminescence characteristics, which aids in the fabrication of high-power white light-emitting diodes. Considering that the NCs are characterized by an inorganic perovskite core and an organic surface layer, we discuss their various structural and surface aspects in this review.